Bibliometric Analysis of the English Musculoskeletal Literature over the Last 30 Years. (27th April 2021) - Loder, Randall T.; Kacena, Melissa A.; Ogbemudia, Blessing; Ngwe, Hervé Nonga; Aasar, Abdul; Ninad, Nehal; Mufti, Osama; Gunderson, Zachary; Whipple, Elizabeth C.
Abstract : Publication and authorship are important in academia for career advancement, obtaining grants, and improved patient care. There has been a recent interest in bibliometric changes over time, especially regarding the gender gap. The purpose of this study was to explore bibliometric changes in the musculoskeletal literature. Bibliometric variables (number of authors, institutions, countries, pages, references, corresponding author position, author gender, geographic region of origin, and editorial board makeup) were analyzed for 5 basic science and 12 clinically oriented musculoskeletal journals from 1985 through 2016. Statistical analyses comprised bivariate analyses, multifactorial ANOVAs, and logistic regression analyses. A p < 0.005 was considered significant. Nearly, all variables increased over time. Asia had the highest number of authors and corresponding author positions, Australia/New Zealand the highest number of institutions and references, North America the highest number of pages, and Europe the highest number of countries. Those with a female first author had more authors, institutions, countries, references, and pages. Likewise, those with a female corresponding author had more authors, institutions, countries, references, and pages. Single-authored manuscripts decreased over time. The percentage of female first authors rose from 10.8% in 1985–1987 to 23.7% in 2015–2016. There were more female 1 st authors in the basic science journals compared to the clinical journals (33.2% vs. 12.7%). Single-authored manuscripts were more likely to be written by males (5.1 vs. 2.4%) and decreased over time. The many differences by geographic region of origin likely reflect different socio/cultural attitudes regarding academia and research, as well as the gender composition of the disciplines by geographic region. Overall, there has been an increase in the number of female 1 st and corresponding authors, editorial board members, and chief editors, indicating a slow but progressive narrowing of the gender gap.